Kam je namenjena poljščina? - Ostromęcka-Frączak, Bożena (Jezik in slovstvo, 2017)
The article presents the results of the most recent research of Polish language and, combined with the author%s own findings, summarises the changes in contemporary Polish language. The emphasis is on new emerging research fields: the functioning of Polish outside Poland, Polish as a foreign/second language, and teaching Polish as a foreign language. In a presentation of how the extralinguistic reality influences language, the author mainly focuses on vocabulary changes, including the rapid increase in the number of neologisms and neosemanticisms. These new lexical items often perform an expressive function, becoming a source of language brutalisation and vulgarisation, a process that is related to the simplification of social relations. The author highlights the reassessment of vocabulary formerly associated only with colloquial language, sociolects or dialects. In her opinion, the observed increase in the number of loanwords from English (especially American English) - although worrying - seems to be a temporary trend that the Polish language will overcome, just as it did in the past. However, she regards shifts in the stylistic system as a potential danger.
Keywords: poljščina; sociolinguistics; sociolingvistika; stilistika; stylistics; leksika